Modern Populism in Greece - Mavrozacharakis, Emmanouil; Tsagarakis, Stelios; Kamekis, Apostolos (2013)
Abstract: Financial crisis has connected Europe with an obvious common pattern which consists the rapidly rise of protest parties that challenge the established political systems. The basic and new feature of these schemes is the intense war rhetoric against the European Union and the vehement rejection of the selected modes of euro rescue. In this sense, populism appears as a new specter haunting European democracies, as active risk, causing serious concerns. Unfortunately, the growing concern does not coincide with policies aiming at finding viable solutions, as the center-right parties and governments believe that the only solution to the crisis is to adopt austerity measures and Social Democrats have not yet found effective alternatives